Industrializing biotechnology: roles of fermentation and bioprocess technology - Ariff, Arbakariya (Universiti Putra Malaysia Press, 2009)
iotechnology is defined by the tools used to practice it. By programming DNA and directing cellular machinery, the products that were unimaginable even 10 years ago could be produced. With biotechnology, the nanoscale machinery of living cells to produce self-contained factories that perform on a characteristic scale of one micron could be established. For industrialization of biotechnology, however, bioproducts and bioenergy must be produced in immense or large quantities to meet market demand. Genetic engineering, for example, is carried out at a molecular scale but is amplified through fermentation and bioprocess technology to transfer the process from the test tube to the bottle through a sequence of integrated steps that generate, recover, purify, formulate and package the product. The challenge facing the fermentation and bioprocess technology discipline is in redirecting the genetic and cellular machinery to make commercially and economically important biomolecules when the cells are placed in controlled environments. Fermentation and bioprocess technology knowledge and skills are applied to design, build and operate hardware and integrated systems that can be used to culture the cells and produce the required products efficiently, as well as to recover, purify and formulate the products in a cost-effective manner to enable the products to be commercialized. In addition, the design and operation of the biomanufacturing process must also follow the regulations set by the authorized bodies prior to commercialization. For example, the current Good Manufacturing Practice (cGMP) regulation set by the Food Drug Authority (FDA) must be adhered to in the production of biopharmaceuticals, while GMP requirements must be applied in food and food ingredient production. The demand for knowledge and skills in fermentation and bioprocess technology continues to grow. This discipline provides a bridge between the research laboratory and the economic, large-scale implementation of biomanufacturing systems. With the rapid growth of biologically based technologies, fermentation and bioprocess technology is needed to solve the problems of today and tomorrow. This lecture describes the basic concept of biomanufacturing processes for the production of various biotechnology products and also the roles of fermentation and bioprocess technology to “Bring Technology To Life” through the conversion of biological materials into other forms needed by mankind. Examples of approaches that have been applied by our research group in the development and improvement of various biomanufacturing processes, such as production of kojic acid, solvents, probiotic microorganisms, metabolites and biopharmaceuticals, using microbials, plant cells and microalgae are highlighted.